Spiro-donor modified blue thermally activated delayed fluorescence emitters with high efficiency, narrowband emission, and excellent lysosomal targeting ability - Deli Li; Qingchao Liu; Ruizhe Xu; Wei Liu; Rong Hu; Wei Li; Shi-Jian Su; Ziyi Ge; Yuhua Tong (Chemical Engineering Journal, 2026)

The ISChip: A high-throughput qPCR array for absolute quantification of insertion sequences across the One Health continuum - Yanyan Zhou; Wen-Jing Zhong; Xin-Li An; Fu-Yi Huang; Xiao-Yu Guo; Meng-Ke Gao; Mei-Rong Xu; Xu Huang; Hu Li; Bangzhou Zhang; Dirk Springael; Jian-Qiang Su (Environmental Pollution, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Priorities for enhancing resilience of SDG causal network from a human-nature perspective - Yiming Su; Guangjin Zhou; Mingyuan Wang; Xiaoyun Li; Tao Liang; Lingqing Wang; Jian Hu; Jixi Gao; Wenwu Zhao; Siyuan Tao; Peter E. Holm; Jörg Rinklebe; et al. (Resources, Conservation and Recycling, 2026)

Short-term ozone exposure and schizophrenia hospitalization risk: temperature modifying effect and greenspace mitigating effect - Chuan Li; Xin Yu; Rong Song; Yanhong Fang; Jiayuan Yang; Zhiyuan Tang; Shaoqi Wang; Xunrong Cheng; Weizhuo Yi; Rubing Pan; Jian Song; Hong Su (Environmental Pollution, 2025)

A BrDof2.4-BrHDA6 module is involved in ABA-CTK-mediating leaf yellowing in Chinese flowering cabbage by affecting histone H3 and H4 acetylation of CCGs - Zhen-liang Mou; Lei Yan; Zong-li Liu; Xin-guo Su; Ze-xiang Zeng; Yuan Rong; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Wei Wei; Jia Si (Postharvest Biology and Technology, 2025)

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

Subseasonal Prediction Skill in the CAMS-CSM Subseasonal-to-Seasonal Forecast System - Yuhan Yan; Jingzhi Su; Boqi Liu; Libin Ma; Xinyao Rong; Bo Liu; Yanli Tang; Jian Li (Advances in Atmospheric Sciences, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

Effects of socioeconomic status and regional inequality on the association between PM2.5 and its components and cardiometabolic multimorbidity: A multicenter population-based survey in eastern China - Zhiqian Cui; Xinxu Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Rong Song; Jintao Liu; Rubing Pan; Weizhuo Yi; Xiaoyu Jin; Jian Song; et al. (Science of The Total Environment, 2024)

Impaired thyroid hormone sensitivity exacerbates the effect of PM2.5 and its components on dyslipidemia in schizophrenia - Jintao Liu; Yinguang Fan; Jian Song; Rong Song; Xuanxuan Li; Li Liu; Ning Wei; Jiajun Yuan; Weizhuo Yi; Rubing Pan; Xiaoyu Jin; Jian Cheng; et al. (Science of The Total Environment, 2024)

High-risk ARGs (HRA) Chip: A high-throughput qPCR-based array for assessment of high-risk ARGs from the environment - Huan-Qin Li; Mei-Rong Xu; Xin-Li An; Hu Liao; Li-Juan Li; Wei Li; Jian-Qiang Su (Water Research, 2024)

Circ-IP6K2 suppresses tumor progression by modulating the miR-1292-5p/CAMK2N1 signal in clear cell renal cell carcinoma - Jian-ying Tang; Lu Yang; Qing-Jian Wu; Ying Yang; Yuan-Yuan Su; Yi-Rong Chen; Jiao Mu (Functional & Integrative Genomics, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Green space and its types can attenuate the associations of PM2.5 and its components with prediabetes and diabetes—— a multicenter cross-sectional study from eastern China - Zhiqian Cui; Rubing Pan; Jintao Liu; Weizhuo Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Li Liu; Ning Wei; Rong Song; Jiajun Yuan; et al. (Environmental Research, 2024)

An updated review of the genus Rhododendron since 2010: Traditional uses, phytochemistry, and pharmacology - Xing-Jian Liu; Hai-Guo Su; Xing-Rong Peng; Hui-Chang Bi; Ming-Hua Qiu (Phytochemistry, 2024)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The global burden of schizophrenia and the impact of urbanization during 1990–2019: An analysis of the global burden of disease study 2019 - Xuanxuan Li; Ning Wei; Jian Song; Jintao Liu; Jiajun Yuan; Rong Song; Li Liu; Lu Mei; Shuangshuang Yan; Yudong Wu; Rubing Pan; Weizhuo Yi; et al. (Environmental Research, 2023)

The association between greenery type and gut microbiome in schizophrenia: did all greenspaces play the equivalent role? - Ning Wei; Shusi Wang; Xuanxuan Li; Rubing Pan; Weizhuo Yi; Jian Song; Li Liu; Jintao Liu; Jiajun Yuan; Rong Song; Jian Cheng; Hong Su (Environmental Science and Pollution Research, 2023)

Characterization of airborne microplastics at different workplaces of the poly(ethylene:propylene:diene) (EPDM) rubber industry - Xiaoni Sun; Rong Song; Jintao Liu; Shuangshuang Yan; Yuxuan Li; Xiaoyu Jin; Yunfeng Liang; Yudong Wu; Lu Mei; Rubing Pan; Weizhuo Yi; Jian Song; et al. (Environmental Science and Pollution Research, 2023)

Sunshine duration and risks of schizophrenia hospitalizations in main urban area: Do built environments modify the association? - Li Liu; Qing Wu; Xuanxuan Li; Rong Song; Ning Wei; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

The impact of hazes on schizophrenia admissions and the synergistic effect with the combined atmospheric oxidation capacity in Hefei, China - Jiajun Yuan; Weiwei Chang; Zhenhai Yao; Liying Wen; Jintao Liu; Rubing Pan; Weizhuo Yi; Jian Song; Shuangshuang Yan; Xuanxuan Li; Li Liu; Ning Wei; et al. (Environmental Research, 2023)

Short-term exposure to air pollution is an emerging but neglected risk factor for schizophrenia: A systematic review and meta-analysis - Rong Song; Li Liu; Ning Wei; Xuanxuan Li; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Lu Mei; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Heat Shock Procedure Affects Cell Division-Associated Genes in Gynogenetic Manipulation - Fan Yu; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Pao Xu; Huan Zhong (Marine Biotechnology, 2022)

Seasonal prediction skills in the CAMS-CSM climate forecast system - Bo Liu; Jingzhi Su; Libin Ma; Yanli Tang; Xinyao Rong; Jian Li; Haoming Chen; Boqi Liu; Lijuan Hua; Renguang Wu (Climate Dynamics, 2021)

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

Effects of simulated drought stress on carotenoid contents and expression of related genes in carrot taproots - Rong-Rong Zhang; Ya-Hui Wang; Tong Li; Guo-Fei Tan; Jian-Ping Tao; Xiao-Jun Su; Zhi-Sheng Xu; Yong-Sheng Tian; Ai-Sheng Xiong (Protoplasma, 2021)

The CMIP6 Historical Simulation Datasets Produced by the Climate System Model CAMS-CSM - Xinyao Rong; Jian Li; Haoming Chen; Jingzhi Su; Lijuan Hua; Zhengqiu Zhang; Yufei Xin (Advances in Atmospheric Sciences, 2021)
This paper describes the historical simulations produced by the Chinese Academy of Meteorological Sciences (CAMS) climate system model (CAMS-CSM), which are contributing to phase 6 of the Coupled Model Intercomparison Project (CMIP6). The model description, experiment design and model outputs are presented. Three members’ historical experiments are conducted by CAMS-CSM, with two members starting from different initial conditions, and one excluding the stratospheric aerosol to identify the effect of volcanic eruptions. The outputs of the historical experiments are also validated using observational data. It is found that the model can reproduce the climatological mean states and seasonal cycle of the major climate system quantities, including the surface air temperature, precipitation, and the equatorial thermocline. The long-term trend of air temperature and precipitation is also reasonably captured by CAMS-CSM. There are still some biases in the model that need further improvement. This paper can help the users to better understand the performance and the datasets of CAMS-CSM.

Simulation of the landform change process on a purple soil slope due to tillage erosion and water erosion using UAV technology - Chao Yang; Zheng-an Su; Jian-rong Fan; Hai-dong Fang; Liang-tao Shi; Jian-hui Zhang; Zhou-yao He; Tao Zhou; Xiao-yi Wang (Journal of Mountain Science, 2020)

Obtaining More Information about Precipitation Biases over East Asia from Hourly-Scale Evaluation of Model Simulation - Nina Li; Jian Li; Xinyao Rong; Haoming Chen; Yufei Xin; Jingzhi Su (Journal of Meteorological Research, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Convectively Coupled Equatorial Waves Simulated by CAMS-CSM - Lu Wang; Tianjun Zhou; Jian Li; Xinyao Rong; Haoming Chen; Yufei Xin; Jingzhi Su (Journal of Meteorological Research, 2019)

Climate Sensitivity and Feedbacks of a New Coupled Model CAMS-CSM to Idealized CO2 Forcing: A Comparison with CMIP5 Models - Xiaolong Chen; Zhun Guo; Tianjun Zhou; Jian Li; Xinyao Rong; Yufei Xin; Haoming Chen; Jingzhi Su (Journal of Meteorological Research, 2019)

A Longitudinal Functional Magnetic Resonance Imaging Study of Working Memory in Patients Following a Transient Ischemic Attack: A Preliminary Study - Wei Su; Jian Guo; Yun Zhang; Jie Zhou; Ning Chen; Muke Zhou; Rong Li; Huafu Chen; Li He (Neuroscience Bulletin, 2018)

The CAMS Climate System Model and a Basic Evaluation of Its Climatology and Climate Variability Simulation - Xinyao Rong; Jian Li; Haoming Chen; Yufei Xin; Jingzhi Su; Lijuan Hua; Tianjun Zhou; Yanjun Qi; Zhengqiu Zhang; Guo Zhang; Jianduo Li (Journal of Meteorological Research, 2018)

An Assessment of CAMS-CSM in Simulating Land–Atmosphere Heat and Water Exchanges - Guo Zhang; Jianduo Li; Xinyao Rong; Yufei Xin; Jian Li; Haoming Chen; Jingzhi Su; Lijuan Hua (Journal of Meteorological Research, 2018)

Inhibitory Effect of Vaginal Lactobacillus Supernatants on Cervical Cancer Cells - Ke-Di Wang; Dong-Jiang Xu; Bao-Ya Wang; Dong-Hui Yan; Zhi Lv; Jian-Rong Su (Probiotics and Antimicrobial Proteins, 2018)

Functional Investigation of a GRIN2A Variant Associated with Rolandic Epilepsy - Xing-Xing Xu; Xiao-Rong Liu; Cui-Ying Fan; Jin-Xing Lai; Yi-Wu Shi; Wei Yang; Tao Su; Jun-Yu Xu; Jian-Hong Luo; Wei-Ping Liao (Neuroscience Bulletin, 2018)

Erratum to: Geometrical feature analysis and disaster assessment of the Xinmo landslide based on remote sensing data - Jian-rong Fan; Xi-yu Zhang; Feng-huan Su; Yong-gang Ge; Paolo Tarolli; Zheng-yin Yang; Chao Zeng; Zhen Zeng (Journal of Mountain Science, 2017)

Geometrical feature analysis and disaster assessment of the Xinmo landslide based on remote sensing data - Jian-rong Fan; Xi-yu Zhang; Feng-huan Su; Yong-gang Ge; Paolo Tarolli; Zheng-yin Yang; Chao Zeng; Zhen Zeng (Journal of Mountain Science, 2017)

Preferable procedure for the screening of syphilis in clinical laboratories in China - Ke-Di Wang; Dong-Jiang Xu; Jian-Rong Su (Infectious Diseases, 2016)

Soil cellulase activity and fungal community responses to wetland degradation in the Zoige Plateau, China - Li-sha Wu; Su Feng; Yuan-yang Nie; Jian-hong Zhou; Zhi-rong Yang; Jie Zhang (Journal of Mountain Science, 2015)

Two new bicyclic sesquiterpenes from the stems of Kadsura heteroclita - Wei Su; Jian-Ping Zhao; Jian Hu; Min Yang; Melissa Jacob; Xiong Cai; Rong Zeng; Sheng-Huang Chen; Hui-Yong Huang; Ikhlas Khan; De-An Guo; Wei Wang (Natural Product Research, 2014)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Isolation and characterization of microsatellite markers for the endangered Taxus yunnanensis - Ying-Chun Miao; Jian-Rong Su; Zhi-Jun Zhang; Hui Li; Jing Luo; Ya-Ping Zhang (Conservation Genetics, 2008)

Development of the male reproductive structures in Taxus yunnanensis - Bing-Yi Wang; Jian-Rong Su; Danilo D. Fernando; Zong-Hui Yang; Zhi-Jun Zhang; Xiao-Ming Chen; Yan-Ping Zhang (Plant Systematics and Evolution, 2008)